Antibody 1A4 with routine immunohistochemistry demonstrates high sensitivity for ALK rearrangement screening of Chinese lung adenocarcinoma patients: A single-center large-scale study. (May 2016) - Wang, Qiushi; Zhao, Lianhua; Yang, Xin; Wei, Shirong; Zeng, Ying; Mao, Chengyi; Lin, Li; Fu, Ping; Lyu, Liang; Li, Zengpeng; Xiao, Hualiang
Highlights: ALK-rearranged candidates prescreening by IHC test using primary antibody 1A4 is a cost-effective choice. The primary antibody 1A4 showed a higher sensitivity than D5F3. D5F3 showed a higher specificity than 1A4. Abstract: Objectives: The rearrangement of echinoderm microtubule-associated protein-like 4-analplastic lymphoma kinase (EML4-ALK) in non-small cell lung cancer (NSCLC) cells might be a promising therapeutic target. However, the low positive rate seeks a reliable and cost-effective method for ALK rearrangement prescreening. This study aimed to evaluate the application of a novel primary antibody 1A4 for routine ALK immunohistochemistry (IHC) test. Materials and methods: Primary antibody 1A4 and D5F3 were used for the screening of 595 formalin-fixed, paraffin-embedded tissues of consecutive patients with lung adenocarcinoma for ALK-positive candidates. Ventana detection system and fluorescence in-situ hybridization (FISH) were used as reference methods. Results: Among 595 cases, the protein expression statuses of 1A4 were 3+ (18), 2+ (50), 1+ (153), and 0+ (374), and those of D5F3 were 3+ (17), 2+ (18), 1+ (20), and 0+ (540). Ventana detection system and FISH test results were successfully obtained from 482 cases. A total of 298 specimens with 1A4 (−) showed 100% concordance with standard FISH results. All 58 FISH (+) cases were identified by antibody 1A4. Meanwhile, 14 and 5 were missed by antibody D5F3 with routine IHC and Ventana system, respectively. 1A4 with routine IHC had better sensitivity (100%, 75.9%, and 91.4%, respectively), but lower specificity (70.3%, 99.8%, and 100%, respectively), than D5F3 with routine IHC and Ventana system. Conclusion: The novel antibody 1A4 used as a prescreening method may help to reduce the false-negative rearranged ALK status if FISH or reverse transcription polymerase chain reaction results were used for validation.